Bee Venom: From Venom to Drug - Abdelwahab Khalil; Basem H. Elesawy; Tarek M. Ali; Osama M. Ahmed (Molecules, 2021)
Insects of the order Hymenoptera have a defensive substance that contains many biologically active compounds. Specifically, venom from honeybees (Apis mellifera) contains many enzymes and peptides that are effective against various diseases. Different research papers stated the possibility of using bee venom (a direct bee sting or in an injectable form) in treating several complications; either in vivo or in vitro. Other reports used the active fractions of bee venom clinically or at labratory scale. Many reports and publications have stated that bee venom and its constituents have multiple biological activities including anti-microbial, anti-protozoan, anti-cancer, anti-inflammatory, and anti-arthritic properties. The present review aims to refer to the use of bee venom itself or its fractions in treating several diseases and counteracting drug toxicities as an alternative protocol of therapy. The updated molecular mechanisms of actions of bee venom and its components are discussed in light of the previous updated publications. The review also summarizes the potential of venom loaded on nanoparticles as a drug delivery vehicle and its molecular mechanisms. Finally, the products of bee venom available in markets are also demonstrated.